Características da precipitação pluviométrica do nordeste brasileiro e seus padrões de acoplamento com as TSM do Pacífico Equatorial e Atlântico Sul. - Coelho, Sergio Carlos Buarque (2010)
The need to establish the long-term precipitation led many authors to try to understand why regulators of interannual climate variability over the Northeast of Brazil. Fluctuations in the equatorial Pacific SST acts as a modulator of climate on various time scales and are associated with the phenomenon (El Niño / Southern Oscillation). We analyzed the patterns of monthly and quarterly precipitation in Northeast Brazil (with emphasis on the eastern part of Northeast Brazil), related to the anomalies of surface temperatures of the equatorial Pacific and south Atlantic, from the SST data obtained from the Comprehensive Ocean-Atmosphere Data System and precipitation data from the universe as we know from Delaware from 1950 to 1999. The monthly precipitation by the phases of the Pacific Decadal Oscillation and rainfall were arranged both quarterly and lag. Were defined conditions of El Niño: positive anomaly; positive derivative; positive derivative if and only if the anomalies were positive and the anomaly index Interoceanic (AI). The best parameter for prediction of quarterly rainfall within the rainy season in NE, was the condition of positive derivative of the SST of the Pacific, one month before the rain (lag1) with positive correlation of 0.3 to 95% of significance, falling to 0.2 (lag2), from February to May versus April-July rainfall. The study confirmed the low levels of correlation, have been mentioned by other authors about the ENE and the SST anomalies in the equatorial Pacific. The monthly mean SST anomalies in the South Atlantic and equatorial Pacific combined showed best results when correlated with monthly precipitation over northern northeast Brazil. On the east of NE was positive correlation of 0.5, on the north of NE was 0.6, decreasing to 0.3 correlation over southern northeast at 95% significance. The two signals combined accounted for (r = 0.7) 49% of the variability in signal Comparable with isolated Pacific, which was correlated with seasonal rainfall. The increase in estimates of rainfall over east of NE occurred from the inclusion of the Atlantic SST anomalies and considered during the calculation of the average normal changes of signal detected in the Pacific Decadal Oscillation.